Pengenalan Digital Pemasaran Terhadap UMKM Lesehan GBK dan Angkringan ganza - Laiven Harnesto Sagala; Nugraeni Nugraeni (Lembaga Pengembangan Kinerja Dosen, 2025)
In the modern era, digital marketing has become the main tactic to make MSMEs more competitive. With a focus on social media, Google My Business (GMB), digital promotions, and collaboration with food delivery platforms, this outreach activity is about the use of digital marketing in Lesehan GBK and Angkringan Ganza MSMEs. These findings indicate important improvements in sales, brand image and market reach. Strategies such as using Instagram for visual content, registering on GMB, special discount promotions, and collaborating with GrabFood and GoFood provide positive contributions. This research emphasizes the importance of digital training for MSME owners to optimize digital platforms. With an integrated approach, MSMEs can develop more competitively in the digital era.